Investigation of Toxic Metals Pollution in Water, Sediment and Fish at Al-Hodeidah city, Red Sea Coast of Yemen - Abdulghany Hameed Ahmed; Mokhtar Al-Abyadh; Fares M.S Muthanna (Information Technology and Science (ITScience), 2024)
The discharge of industrial waste and sewage is unequivocally the primary cause of toxic metal pollution in the Red Sea. This study centers on the detrimental impact of these human activities on the coastal ecosystem. We did an investigation because there was no available data on the levels of hazardous metals in the Red Sea Coast of Yemen. This study analyzes the average levels of toxic metals - Pb, Cd, Hg, and As - in water, sediments, and various fish organs including muscle, liver, and gill. Acquired from Al-Hodeidah city, situated on the Red Sea Coast of Yemen. Examples of water and debris have been gathered at nine different locations. Four fish species (Lethrinus mahsena, Epinephelus areolatus, Thunnus tonggol, and Sphyraena jello) were acquired from local commercial fisherman in Al-Hodeidah city between 2022 and 2023. Pb, Cd, Hg, and As levels were tested in water at 0.053-0.105, 0.006-0.008, 0.006-0.008, and 0.007-0.009 mg/l respectively. In sediment, the levels were 75.883-77.059, 2.380-2.495, 0.011-0.028, and 0.091-0.109 ?g/g dry weight for Pb, Cd, Hg, and As respectively. Levels of toxic metals in fish tissue (?g/g dry weight) vary as follows: Pb 0.031-0.357, Cd 0.018-0.146, Hg 0.019-0.082, and As 0.044-0.121 ?g/g dry weight in muscle; Pb 0.058-1.466, Cd 0.057-0.700, Hg 0.009-0.044, and As 0.011-0.074 dry weight in gills; and Pb 0.049-0.999, Cd 0.047-0.705, Hg 0.051-0.186, and As 0.065-0.198 ?g/g dry weight in liver cells. Comparing data from local and international studies along with global and local contamination standards, it is clear that pollution concentrations in Yemen are currently lower than the established limits